Тhe problem resource evaluation sniper barrel weapons and sport - Писаренко, В.Г. (Problems of Tribology, 2016)
The results of calculation of stress-strain state trunks sports and sniper weapons. Based on analysis of the estimated impact of changes in the coefficient of friction on the characteristics of the stress-strain state trunk routes specified resource definition and evaluation of ways to improve the wear-resistance tribosystems in conditions of high friction.